Penerapan Kurikulum Merdeka pada pembelajaran IPAS kelas IV di SD Negeri Tahunan Yogyakarta - Purba, Peronika; Rahayu , Ayu; Murniningsih, Murniningsih (Rafandha Press, 2023)
Background: SD Negeri Tahunan is not yet a driving school, but SD Negeri Tahunan is one of the schools that has implemented the Phase B independent curriculum (grades I and IV), and the independent curriculum implemented in this school, namely the independent independent curriculum, has changed. Purpose: This study aims to describe the planning, implementation, and evaluation of science learning based on the independent curriculum in class IV SD Negeri Tahunan Yogyakarta. Method: The design of this study uses descriptive qualitative. Data collection techniques through observation, interviews and documentation. This research data analysis technique uses the Miles and Huberman analysis model. Findings: The results of this study indicate that: (1) the science lesson plan made by the teacher has been adjusted to the criteria for an independent curriculum, the teacher has analyzed learning outcomes, made learning objectives, learning goal lines, methods, models, approaches, materials, learning resources, assessments, then poured into teaching modules, (2) the implementation of science learning in class IV is carried out in accordance with the lesson plans that have been made previously. Teachers create collaborative, interactive, and contextual learning. Activities in science learning vary so that learning is easy to understand, not boring, fosters an attitude of independence, high responsibility and curiosity, and makes learning fun, (3) the form of evaluation of science learning in class IV SD Negeri Tahunan is carried out by carrying out diagnostic assessments, formative assessments and summative assessments. The diagnostic assessment that has been carried out is a non-cognitive diagnostic assessment. Formative assessments are given by the teacher at the end of science learning at each meeting. Summative assessments are carried out during daily assessments, midterm assessments, and end of semester assessments.